Examining mediator effects within multilevel perspectives: a comprehensive analysis of job uncertainty and job stress - Ding, Alyssa Y L * (2024)
Job stress is a growing problem in the work literature as employees continue to keep up with the demands of a growing and competitive environment due to globalization and the Industrial Revolution 4.0. Coupled with job uncertainty due to unpredictable environments that interrupt regular workflow, the issue of job stress in the workforce is further escalated as employees face ambiguity in predicting the direction of the future of their work. The present study aims to understand the relationships between environmental factors (i.e., technological uncertainty), organisational factors (i.e., clan culture and learning opportunities), individual factors (i.e., emotional intelligence and proactive personality), and individual resources (i.e., problem-solving skills, entrepreneurship skills, and technological readiness) that contributes to job uncertainty, and consequently job stress as initially proposed by Robbins and colleagues (2009). In addressing the lack of studies on how technological uncertainty and clan culture relate to learning opportunities as well as how emotional intelligence and proactive personality relate to problem-solving skills, entrepreneurship skills, and technological readiness, and how these constructs further relate to job uncertainty and job stress, this study employs a successive independent samples research design to address the limitations of the cross-sectional design and longitudinal design. In Study 1, the relationships between job uncertainty and job stress, technological uncertainty, clan culture, and learning opportunities, as well as emotional intelligence, proactive personality, problem-solving skills, entrepreneurship skills, and technological readiness is tested at an individual level for 252 employees aged 18-years old and above (M = 30.75 years; SD = 8.7 years). In Study 2, the relationships between these constructs by collecting another set of data, recruiting 240 employees from 36 teams aged 18-years old and above (M = 38.0 years; SD = 8.6 years), targeting teams from organisations with technological uncertainty and clan culture as multilevel constructs to further examine if they have cross-level relationships on job uncertainty. To analyse the results, hierarchical linear regression analysis was used for Study 1 while hierarchical linear modelling analysis was used for Study 2. The general results showed that job uncertainty significantly predicts job stress in a positive direction, learning opportunities significantly negatively predicts job uncertainty, and technological uncertainty and clan culture positively affect learning opportunities. Specifically, in Study 1, emotional intelligence was found to significantly predict entrepreneurship skills, and proactive personality was found to predict entrepreneurship skills and technological readiness. In Study 2, emotional intelligence was found to significantly predict problem solving skills and entrepreneurship skills, while proactive personality was found to predict problem-solving skills, entrepreneurship skills, and technological readiness. Mediation analyses were also conducted to further understand the relationships between the variables in the study. Implications and recommendations for future studies are discussed with regard to leadership and organisational management whereby a more supportive leadership like clan culture is beneficial in dealing with job uncertainty and job stress, emphasizing the multilevel nature of the issue of job uncertainty and job stress. The study also highlights the importance of learning opportunities in organisational training and development in the context of technological uncertainty and job uncertainty.